Casting a Movement The Welcome Table Initiative - Syler, Claire; Banks, Daniel (Taylor & Francis, 2019)
"Casting a Movement brings together US-based actors, directors, educators, playwrights, and scholars to explore the cultural politics of casting. Drawing on the notion of a ""welcome table""-a space where artists of all backgrounds can come together as equals to create theatre-the book's contributors discuss casting practices as they relate to varying communities and contexts, including Middle Eastern American theatre, Disability culture, multilingual performance, Native American theatre, color- and culturally-conscious casting, and casting as a means to dismantle stereotypes. Syler and Banks suggest that casting is a way to invite more people to the table so that the full breadth of US identities can be reflected onstage, and that casting is inherently a political act; because an actor's embodied presence both communicates a dramatic narrative and evokes cultural assumptions associated with appearance, skin color, gender, sexuality, and ability, casting choices are never neutral. By bringing together a variety of artistic perspectives to discuss common goals and particular concerns related to casting, this volume features the insights and experiences of a broad range of practitioners and experts across the field. As a resource-driven text suitable for both practitioners and academics, Casting a Movement seeks to frame and mobilize a social movement focused on casting, access, and representation."